Indicators of fatal outcome in severe Plasmodium falciparum malaria: A study in a tertiary-care hospital in Thailand - Noppadon Tangpukdee (2018)
Objective: To illustrate the clinical features and investigate the indicators associated with a fatal outcome in adult patients with severe Plasmodium falciparum malaria admitted to the Hospital for Tropical Diseases, Bangkok, Thailand. Methods: We studied 202 adult malaria patients admitted to the Intensive Care Unit. A total of 43 clinical variables were identified by univariate and logistic regression analyses, to eliminate confounding factors. Results: Regarding the statistical methods, only 6 variables-jaundice, cerebral malaria, metabolic acidosis, body mass index, initial respiratory rate, and white blood cell count-were significant indicators of death, with adjusted odds ratios (95% CI) of 15.2 (2.1-32.3), 4.3 (2.3-12.6), 3.3 (2.3-5.7), 2.4 (1.9-3.5), 2.2 (1.5-2.6), and 1.7 (1.2-3.1), respectively. Conclusion: Our study found that jaundice, cerebral malaria, metabolic acidosis, body mass index, initial respiratory rate and white blood cell count were indicators of fatal outcome in severe Plasmodium falciparum malaria. Further studies on the fatal indicators in severe malaria need to be compared with data from different geographical areas, to construct practical measures to address potentially fatal indicators in different settings. © 2010 Hainan Medical College.